Evaluating the Impact of Training Techniques and Physical Performance on the Development of Court Tennis Drive Stroke Skills: A Literature Review - Nugroho, Djoko; Syaifullah, Rony; Sabarini, Sri Santoso; Liskustyawati, Hanik; Putro, Baskoro Nugroho; Jariono, Gatot (Physical Education Theory and Methodology, 2024)
Objectives. The objective of the study was to develop a training program and improve physical performance through a review of the literature in order to enhance the field tennis drive stroke. Materials and methods. A comprehensive analysis of earlier research was carried out, comprising a review of articles published between 2019 and 2024 that discuss ways to improve the physical condition of volleyball players. Electronic searches were conducted using SPORTDiscus, PubMed, Google Scholar, Web of Science, and Scopus. The articles addressing the most effective methods for enhancing court tennis drive stroke abilities through physical performance and practice techniques were then compiled. Results. The findings of this study indicate that forty articles used physical performance techniques and practice to enhance the court tennis drive stroke. Based on the physical state assessments and its subsequent improvements, items were categorised.Anaerobic speed endurance has been defined as a training method that may be used by an athlete. Conclusions. The following conclusions were reached after a thorough analysis: while physical performance includes muscle strength, aerobic and anaerobic endurance, speed and acceleration, explosiveness, flexibility, agility, and balance, a number of training regimens were found to be effective in improving the skills of the court tennis drive stroke. These training methods include circuit training, strength training, endurance training, kinesthetics’ perception training, shadow sports training, rope ball training, interval training, and training frequency.